Mineral and Matrix Changes in Brtl/+ Teeth Provide Insights into Mineralization Mechanisms. (29th May 2013) - Boskey, Adele L.; Verdelis, Kostas; Spevak, Lyudmila; Lukashova, Lyudmila; Beniash, Elia; Yang, Xu; Cabral, Wayne A.; Marini, Joan C.
Abstract : The Brtl/+ mouse is a knock-in model for osteogenesis imperfecta type IV in which a Gly349Cys substitution was introduced into one COL1A1 allele. To gain insight into the changes in dentin structure and mineral composition in these transgenic mice, the objective of this study was to use microcomputed tomography (micro-CT), scanning electron microscopy (SEM), and Fourier transform infrared imaging (FTIRI) to analyze these structures at 2 and 6 months of age. Results, consistent with the dental phenotype in humans with type IV OI, showed decreased molar volume and reduced mineralized tissue volume in the teeth without changes in enamel properties. Increased acid phosphate content was noted at 2 and 6 months by FTIRI, and a trend towards altered collagen structure was noted at 2 but not 6 months in the Brtl/+ teeth. The increase in acid phosphate content suggests a delay in the mineralization process, most likely associated with the defect in the collagen structure. It appears that in the Brtl/+ teeth slow maturation of the mineralized structures allows correction of altered mineral content and acid phosphate distribution.